2021
DOI: 10.3390/joitmc7010088
|View full text |Cite
|
Sign up to set email alerts
|

FinTech in the Small Food Business and Its Relation with Open Innovation

Abstract: Small food businesses have difficulty accessing banks for financing. The growth of the sharing economy through financial technology (FinTech) makes it possible for small enterprises to receive access for credit. However, not all small business owners want to receive financing from FinTech companies. This study aims to analyze factors affecting FinTech adoption in small enterprises and its impact on business sustainability. The modified UTAUT 2 model was applied in this study. There were 184 small food business… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 71 publications
(131 reference statements)
8
36
0
1
Order By: Relevance
“…In most countries across the globe, SMEs have an important role to support long-term economic growth; thus, they are growing rapidly (Ajayi, Odusanya, & Morton, 2017;Najib, Ermawati, Fahma, Endri, & Suhartanto, 2021). However, the capability of SMEs to recruit and employ professional staff is limited due to their limited resources (Haruna & Marthandan, 2017;Suhartanto & Leo, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In most countries across the globe, SMEs have an important role to support long-term economic growth; thus, they are growing rapidly (Ajayi, Odusanya, & Morton, 2017;Najib, Ermawati, Fahma, Endri, & Suhartanto, 2021). However, the capability of SMEs to recruit and employ professional staff is limited due to their limited resources (Haruna & Marthandan, 2017;Suhartanto & Leo, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have examined FinTech as an outcome of the development and growth of blockchain and artificial intelligence technologies (Fernandez-Vazquez et al 2019 ; Cumming et al 2022 ; Goodell et al 2021 ; Kumar et al 2022 ) as well as digital transformation (Dorfleitner et al 2022 ). Several recent studies have explored the role of FinTech in improving financial innovation (Menne et al 2022 ; Najib et al 2021 ; Shin and Choi 2019 ; Zhao et al 2019 ) and ensuring sustainable development (Deng et al 2019 ). With regards to the sustainability, several studies have examined the contribution of FinTech in banking sector (Ji and Tia 2022 ; Kangwa et al 2021 ; Saif et al 2022 ), while others introduced the concept of green FinTech sustainability (Puschmann et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies using TPB (Nystrand and Olsen, 2020; Najib et al , 2021a) noted that attitude had become an important variable that affects purchase intention. Numerous studies (Nguyen et al , 2019; Nystrand and Olsen, 2020) have shown that the variable of attitude is the antecedent that has the most significant influence on purchase intention compared to other variables in the TPB model.…”
Section: Discussion and Implicationmentioning
confidence: 99%